2019
DOI: 10.1634/theoncologist.2019-0628
|View full text |Cite
|
Sign up to set email alerts
|

Supervised, Multimodal Exercise: The Chemotherapy Supportive Therapy That Almost Does It All

Abstract: Delivery of full chemotherapy dose intensity with minimization of adverse chemotherapy-related events is a primary quality of care indicator in medical oncology. Clinical oncology professionals are also increasingly recognizing patient quality of life as a vital component of cancer care [1]. As such, a therapy that could maximize delivery of chemotherapy relative dose intensity (RDI), reduce treatment toxicities, and improve quality of life, with positive side effects of improved physical fitness, reduced anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A reimbursement strategy is currently unavailable for individuals with cancer participating in cardiac rehabilitation, highlighting the need to demonstrate the effectiveness of these programs in this population (10). In cardiac populations, cardiac rehabilitation has been found to be cost-effective relative to no cardiac rehabilitation, but the most cost-effective delivery model is unclear (65,73). In cancer survivors, exercise physiologistor physiotherapist-led physical activity programs have been shown to be more cost-effective compared to home-based selfmanagement programs (74).…”
Section: Program Fundingmentioning
confidence: 99%
“…A reimbursement strategy is currently unavailable for individuals with cancer participating in cardiac rehabilitation, highlighting the need to demonstrate the effectiveness of these programs in this population (10). In cardiac populations, cardiac rehabilitation has been found to be cost-effective relative to no cardiac rehabilitation, but the most cost-effective delivery model is unclear (65,73). In cancer survivors, exercise physiologistor physiotherapist-led physical activity programs have been shown to be more cost-effective compared to home-based selfmanagement programs (74).…”
Section: Program Fundingmentioning
confidence: 99%
“…It is in line with Friedman's theory that supportive therapy is a place where a group exchanges experiences and supports each other to reduce anxiety. Pardede asserts that supportive therapy is effective for various psychiatric disorders and medical conditions, such as schizophrenia, bipolar disorder, depression, personality disorders, substance abuse, and anxiety [32]. Supportive therapy is carried out by exploring individual abilities, analyzing sources of family support and outside, and evaluating them.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although the reason for this regimen-specific effect is unknown, it has been suggested that there may be greater potential for exercise to improve tolerance when tolerance is lower. 21 Although highly toxic, anthracyclines are also among the most effective for treatment of breast cancer, 20 and therefore interventions to reduce the risk of dose-limiting toxicities for anthracycline-based regimens are critical. There was also a positive effect of exercise on prevention of weight gain during docetaxel 1 cyclophosphamide chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 99%